2012
DOI: 10.1128/aem.06770-11
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Five Anaerobic Toluene-Degrading Microbial Communities Investigated Using Stable Isotope Probing

Abstract: Time-series DNA-stable isotope probing (SIP) was used to identify the microbes assimilating carbon from [ 13 C]toluene under nitrate-or sulfate-amended conditions in a range of inoculum sources, including uncontaminated and contaminated soil and wastewater treatment samples. In all, five different phylotypes were found to be responsible for toluene degradation, and these included previously identified toluene degraders as well as novel toluene-degrading microorganisms. In microcosms constructed from granular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 68 publications
(60 reference statements)
2
58
0
Order By: Relevance
“…The high abundance of Firmicutes in TOLDC and NAPDC is consistent with recent reports of anaerobic monoaromatic hydrocarbon-degrading cultures that implicate Firmicutes (for example, Peptococcaceae) as primary hydrocarbon degraders (Abu Laban et al, 2009;Winderl et al, 2010;Sun and Cupples, 2012;Fowler et al, 2014) or playing key roles alongside Deltaproteobacteria (Ficker et al, 1999;Ulrich and Edwards, 2003;Sakai et al, 2009). In contrast, members of the Deltaproteobacteria, particularly Syntrophus/Smithella sp., have been implicated in methanogenic alkane degradation, particularly of longer-chain alkanes (Zengler et al, 1999;Gray et al, 2011;Cheng et al, 2013).…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingsupporting
confidence: 74%
See 1 more Smart Citation
“…The high abundance of Firmicutes in TOLDC and NAPDC is consistent with recent reports of anaerobic monoaromatic hydrocarbon-degrading cultures that implicate Firmicutes (for example, Peptococcaceae) as primary hydrocarbon degraders (Abu Laban et al, 2009;Winderl et al, 2010;Sun and Cupples, 2012;Fowler et al, 2014) or playing key roles alongside Deltaproteobacteria (Ficker et al, 1999;Ulrich and Edwards, 2003;Sakai et al, 2009). In contrast, members of the Deltaproteobacteria, particularly Syntrophus/Smithella sp., have been implicated in methanogenic alkane degradation, particularly of longer-chain alkanes (Zengler et al, 1999;Gray et al, 2011;Cheng et al, 2013).…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingsupporting
confidence: 74%
“…Many previous studies have shown that microbial communities in methanogenic hydrocarbonassociated environments (for example, Chang et al, 2005;Kasai et al, 2005;Sun and Cupples, 2012;Wawrik et al, 2012;An et al, 2013) or enrichment cultures (Ficker et al, 1999;Fowler et al, 2012) can be highly diverse. Literature-wide compilations examining such communities (Gray et al, 2011;Strapoc et al, 2011;Kleinsteuber et al, 2012) have revealed that they frequently contain hydrogenotrophic (for example, Methanoculleus, Methanolinea, Candidatus Methanoregula, Methanospirillum), acetotrophic (for example, Methanosaeta), and/or methylotrophic methanogens (for example, Methanolobus; Wuchter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, additional environmental parameters should be considered and measured combined with more sampling times over years. Furthermore, the diversity of the archaeal and eukaryotic community based on the high-throughput and sensitive sequencing technology should be combined with environmental characteristics to establish a more exact relationship between biogeochemistry cycling and microbial communities in drinking water reservoirs [64]. Despite the fact that there may have been some disturbances, the comparison of the communities detected in our study was feasible, since all samples were treated similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Other abundant genera were less expected. For example, Azoarcus is an organism studied for its abilities to degrade soil contaminants (33), and Pectobacterium (Gammaproteobacteria) is known primarily as a plant pathogen (34). Indeed, although The models for the individual pathways are based on the residual frequencies of the pathway after correcting for the Total N pathway frequency (see text).…”
Section: Resultsmentioning
confidence: 99%